ANALISIS KINERJA JALAN DALAM UPAYA MENGATASI KEMACETAN LALU LINTAS PADA RUAS SIMPANG BERSINYAL DI KOTA PALU - Alhadar, Ali (SMARTek, 2011)
Traffic congestion caused by traffic volume close to road capacity, where the service level canbe seen from the degree of saturation, ie DS = V / C. Ideally the value of V / C â‰¤ 0.75. From visualobservations the author, in Palu has frequent traffic congestion especially at peak hours on aparticular road segment. One reason is the high vehicle growth is not matched by growth inroad infrastructure. The purpose of this paper is to evaluate the performance of the streetbetween two signalized intersections in the city of Palu to determine the causes and findsolutions solving traffic congestion.The survey will be conducted to obtain primary data and secondary data analysis required inthe performance of such road traffic data, data geometric road side barriers, interviews withpassengers and motorists. The study was conducted for 4 days at 06:00 to 22:00 with theassumption that the traffic data coverage is 93%.This paper recommends a treatment that is optimized bersinyal roads by managing theintersections along the road segment between intersections with traffic cut off by installing asignal light and each intersection there is an alternative to motorists to avoid congestion, afterallowing back off to prevent the flow of traffic queues length.